NADPH oxidase activity and reactive oxygen species production in brain and kidney of adult male hypertensive Ren-2 transgenic rats - Vokurková, M; Rauchová, H; Řezáčová, L; Vaněčková, I; Zicha, J (Physiological research, 2015)
Hypothalamic paraventricular nucleus (PVN) and rostral ventrolateral medulla (RVLM) play an important role in brain control of blood pressure (BP). One of the important mechanisms involved in the pathogenesis of hypertension is the elevation of reactive oxygen species (ROS) production by nicotine adenine dinucleotide phosphate (NADPH) oxidase. The aim of our present study was to investigate NADPH oxidase-mediated superoxide (O(2)(-)) production and to search for the signs of lipid peroxidation in hypothalamus and medulla oblongata as well as in renal medulla and cortex of hypertensive male rats transgenic for the murine Ren-2 renin gene (Ren-2 TGR) and their age-matched normotensive controls - Hannover Sprague Dawley rats (HanSD). We found no difference in the activity of NADPH oxidase measured as a lucigenin-mediated O(2)(-) production in the hypothalamus and medulla oblongata. However, we observed significantly elevated NADPH oxidase in both renal cortex and medulla of Ren-2 TGR compared with HanSD. Losartan (LOS) treatment (10 mg/kg body weight/day) for 2 months (Ren-2 TGR+LOS) did not change NADPH oxidase-dependent O(2)(-) production in the kidney. We detected significantly elevated indirect markers of lipid peroxidation measured as thiobarbituric acid-reactive substances (TBARS) in Ren-2 TGR, while they were significantly decreased in Ren-2 TGR+LOS. In conclusion, the present study shows increased NADPH oxidase activities in renal cortex and medulla with significantly increased TBARS in renal cortex. No significant changes of NADPH oxidase and markers of lipid peroxidation were detected in the studied brain regions.
Keywords: NADPH-oxidasy; Random Allocation; Male; Hypertension; mužské pohlaví; Losartan; NADPH Oxidases; mozek; superoxidy; Lipid Peroxidation; blokátory receptorů AT1 pro angiotensin II; Rats, Transgenic; Angiotensin II Type 1 Receptor Blockers; Brain; zvířata; náhodné rozdělení; ledviny; hypertenze; Superoxides; potkani transgenní; Kidney; peroxidace lipidů; losartan; Animals